Government Incentives and Comparative Advantage of the Sheep Industry in Malaysia - Mohamed, Zainal Abidin; Chiew, Eddie Fook Chong; Shamsudin, Mad Nasir (Universiti Putra Malaysia Press, 1995)
This study computes the protection rates and comparative advantage of sheep production from an import substitution perspective. The results show that, in general, sheep production in Malaysia is moderately protected as shown by the tpR. Domestic price is about 32% above the world price. The value of ETr, on the other hand, indicates that there is an overall net incentive in sheep production. In terms of comparative advantage, this implies that with a small herd size, sheep production is not viable economically and socially.